2023
DOI: 10.1371/journal.pone.0280052
|View full text |Cite
|
Sign up to set email alerts
|

Involving men in cervical cancer prevention; a qualitative enquiry into male perspectives on screening and HPV vaccination in Mid-Western Uganda

Abstract: Introduction Evidence-based preventive strategies for cervical cancer in low-resource setting have been developed, but implementation is challenged, and uptake remains low. Women and girls experience social and economic barriers to attend screening and human papillomavirus (HPV) vaccination programs. Male support has been proven successful in uptake of other reproductive healthcare services. This qualitative study with focus groups aimed to understand the perspectives of males on cervical cancer screening and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…This makes men a critical target for impactful communication and other interventions aimed at increasing screening uptake. Men and their involvement in the control of cervical cancer are key players in the elimination of cervical cancer [9,10,11]. In this study men had signi cant better health seeking behaviour compared to the women.…”
Section: Male Involvementmentioning
confidence: 58%
See 1 more Smart Citation
“…This makes men a critical target for impactful communication and other interventions aimed at increasing screening uptake. Men and their involvement in the control of cervical cancer are key players in the elimination of cervical cancer [9,10,11]. In this study men had signi cant better health seeking behaviour compared to the women.…”
Section: Male Involvementmentioning
confidence: 58%
“…Good knowledge among men would enable them to embrace the prevention programmes and also to support and encourage the women to go for screening and to seek medical help on acquisition of symptoms of cervical cancer. [10] Poor recognition of cancer symptoms by both patients and primary healthcare professionals may contribute to the advanced stage at diagnosis and poor survival of cervical cancer patients in Uganda [11,12]. Ugandan women with vaginal symptoms often rst attribute their symptoms to gynaecological infections such as candidiasis and sexually transmitted infections.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a lack of male partner support is a well-documented barrier to the uptake of cervical cancer prevention-related interventions in sub-Saharan Africa. [19][20][21][22][23][24] Specific to the potential use of intravaginal therapies for cervical precancer treatment, male partner support is crucial, as these therapies often require periods of abstinence during their use. Though there is limited literature on intravaginal topical therapies for the prevention of cervical cancer in LMICs, studies on the use of intravaginal microbicides for HIV prevention among women in Sub-Saharan Africa have shown that male partner support is essential to uptake and adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Limited knowledge among men about the risk factors and causes of cervical cancer can limit uptake of screening. Increased knowledge among men would enable them to embrace the prevention programs and also to support and encourage the women to go for screening and to seek medical help on acquisition of symptoms of cervical cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%